2020
DOI: 10.3389/fpls.2020.601009
|View full text |Cite
|
Sign up to set email alerts
|

The Threat of the Combined Effect of Biotic and Abiotic Stress Factors in Forestry Under a Changing Climate

Abstract: Plants encounter several biotic and abiotic stresses, usually in combination. This results in major economic losses in agriculture and forestry every year. Climate change aggravates the adverse effects of combined stresses and increases such losses. Trees suffer even more from the recurrence of biotic and abiotic stress combinations owing to their long lifecycle. Despite the effort to study the damage from individual stress factors, less attention has been given to the effect of the complex interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 200 publications
(324 reference statements)
0
72
0
1
Order By: Relevance
“…Interestingly, in a recent study on the combination of high light and heat stress it was found that heat stress-driven regulation of stomata (stomata opening) overcomes high light-driven stomata regulation (stomata closure) to result in stomata opening during the stress combination [47]. In addition to stomatal responses, root architecture is also altered during a stress combination [58,59], and nutrient availability plays a key role in this response [58,60,61]. In addition to studies examining the simultaneous exposure of plants to two or more stresses (described in the preceding text), studies of sequential exposure of plants to different stresses, or their combination, revealed a similar complexity in plant responses to a stress combination [61][62][63].…”
Section: The Impact Of Multifactorial Stress Combinations On Plant Mementioning
confidence: 99%
“…Interestingly, in a recent study on the combination of high light and heat stress it was found that heat stress-driven regulation of stomata (stomata opening) overcomes high light-driven stomata regulation (stomata closure) to result in stomata opening during the stress combination [47]. In addition to stomatal responses, root architecture is also altered during a stress combination [58,59], and nutrient availability plays a key role in this response [58,60,61]. In addition to studies examining the simultaneous exposure of plants to two or more stresses (described in the preceding text), studies of sequential exposure of plants to different stresses, or their combination, revealed a similar complexity in plant responses to a stress combination [61][62][63].…”
Section: The Impact Of Multifactorial Stress Combinations On Plant Mementioning
confidence: 99%
“…In nature, plants are simultaneously exposed to a combination of biotic and abiotic stresses (Ramegowda and Senthil-Kumar, 2015 ; Pandey et al, 2017 ; Teshome et al, 2020 ). In a previous study, our group used molecular methods to investigate the individual effects of P. cinnamomi and drought, which are the two main stresses leading to oak decline (Jorge et al, 2006 ; Echevarría-Zomeño et al, 2009 ; Sghaier-Hammami et al, 2013 ; Valero-Galván et al, 2013 ; Simova-Stoilova et al, 2015 , 2018 ; San-Eufrasio et al, 2020 ), on Q. ilex seedlings and their response to these two stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant signs of climate change are elevated mean surface temperature, ice melting, sea level rise and extreme weather events [ 3 , 4 ]. As a result of these rapid global alterations, crops are increasingly facing abiotic stresses, mainly drought, salinity and heat stress [ 2 , 9 , 12 , 13 ]. The demand for food is constantly increasing due to the growing population.…”
Section: Introductionmentioning
confidence: 99%